Fait Divers e Estesia : o sensacionalismo revelado nas narrativas do Já Paraíba - Melo, Dina Pereira de (2018)
Sensationalism history have been closely following Press history from the start. Nowadays, publishing ethical concerns question why such hard earned values in Brazil, like ethics, are neglected or weakened when journalism practices sensationalism, considering it has costed the lives of many publicists. This study investigates the creation of verbal discourses in Já Paraíba, an unashamedly sensationalist daily newspaper from the state of Paraíba, focusing on two tragedies: the criminal cases of Fernanda Ellen (2013) and Goiana (2015), in which, respectively, one girl and two women were murdered in João Pessoa, the capital of the state. It also aims to study what strategies the newspaper uses to persuade the reader, with an emphasis on sensational characteristics. An amount of 32 published articles and covers were selected, from the first investigations to the explanation of the crimes, when the alleged perpetrators were arrested. We applied in the analysis the principles of Greimasian semiotics, which consider the text a meaningful whole, whose message is understood in a sequence of levels. That was connected to the notion of ethos developed by D. Maingueneau and to the mimetic games of time in narrative, by Paul Ricoeur. Based on the discourse strategies that the newspaper pursued, we looked into which effects of meaning they used to forge a recognizable style intended to keep readers interest. As a result, the investigation proposes that the flexible ethics in Já newspaper spread fait divers all over the news practices. Their discourse depicts a world divided between the forces of good and evil, surrounded by an atmosphere of mystery, gossip and thirst for revenge, and it is dramatic to the point of making the sensations more relevant than the information.